Integration of satellite surveillance and metagenomics for the monitoring and protection of water basins from oil spills - Emilio D'Ugo; Arghya Mukherjee; Roberto Giuseppetti; Matteo Tucci; Paola Bucci; Federico Aulenta; Giovanni Laneve; Fabio Magurano (Environmental Advances, 2024)
The planetary crisis regarding water resources means that new methods are needed to monitor large areas of water basins that are threatened by chemical and natural pollutants, together with climate change. With the aim to detect oil spill, we applied an algorithm, which could consistently and reliably confirm the presence of oil in four polluted lake waters analyzed. Combined algorithm application and metagenomic analysis from the spill areas that had been detected by the satellite identified drivers of the microbial response to oil pollution. Based on ortholog abundances, metabolic pathway reconstruction carried out in PICRUSt2 highlighted the degradative capacity of these microorganism. These microorganisms could be suitable candidates for treatment of crude oil, aromatic hydrocarbons and the desulfurization of persistent petroleum substances like dibenzothiophene.Environmental changes have been analysed with the combination of satellite monitoring and metagenomic in other studies. Red snow phenomenon, in Franz Josef Land's Arctic observed by satellite, is the result of a microbial succession dominated by Chlamydomonas nivalis, a unicellular, red-colored photosynthetic green algae. Similarly, satellite monitoring and metagenomic monitoring were used to assess the impact on coral reefs of a huge quantity of mud spill from iron ore mining on the Abrolhos Bank reef in Brazil.In our study, the combination of satellite sensing and metagenomics analyses offer useful tools for the real-time monitoring of water bodies threatened by oil spills, as well as for the design of recovery strategies based on the use of valuable hydrocarbonoclastic microorganisms.